Technology-Based Video Analysis for Evaluating Pedagogical Competence of Prospective Elementary School Teachers Using Gagné’s Conditions of Learning - Syahrial, Syahrial; Asrial, Asrial; Haryanto, Haryanto (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to examine the use of digital learning videos as a technology-based assessment tool to evaluate the pedagogical competence of prospective elementary school teachers using Gagné’s Conditions of Learning framework. Methodology: A qualitative descriptive method supported by simple quantitative analysis was employed by analyzing 20 digitally recorded learning videos from a Teacher Professional Education program. A structured video analysis rubric was applied as a form of technology-mediated observation to identify pedagogical indicators, including responding, reinforcement, retrieval, and generalization. Main Findings: The findings indicate that digital video analysis effectively captures pedagogical practices, with responding (43.5%) and reinforcement (29.0%) dominating classroom interactions, while retrieval (14.5%) and generalization (13.0%) appear less frequently. The use of video as a digital medium enables detailed, repeatable, and objective observation of instructional practices across different teaching contexts. Novelty/Originality of this study: This study contributes to educational technology research by integrating classical learning theory with video-based digital assessment, offering a scalable and evidence-based approach for evaluating teacher pedagogical competence in professional education programs.